The Effectiveness Of Productive ZIS Funds On SMEs Affected By Covid-19 - Hakimi, Fifi; Niswah, Farokhah Muzayinatun; Mafruudloh, Naajihah (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to determine how effective the distribution of productive zakat, infaq, alms funds to SMEs affected by COVID-19 and to find out the model for distributing ZIS productive funds in improving the welfare of SMEs. The method used is a mixed method to produce more comprehensive facts. This study indicates that in the empowerment program, there is a training program held by the amil zakat institution as a form of business assistance that can increase the income of mustahiq SMEs. This program has quite effective impact on SMEs affected by COVID-19. Researchers found an effective ZIS fund distribution mechanism model with a business assistantship that amil zakat institutions must carry out through business development training programs, spiritual improvement, and financial planning. This study aims to improve the skills, faith, and finances of the mustahiq so that they can achieve a level of welfare.